The Role of Teachers' Professional Competence on the Learning Achievement of Group a Students at TK Al Jamiatul Amaliyah Gerumpung - Melia Rahmawati; Ayatullah (Formad English Foundation NTB-Jakarta, 2024)
This research was conducted with the objectives: 1) To determine the competence of professional teachers in TK Al Jami'atul Amaliyah Gerumpung, 2) To determine student achievement in TK Al Jami'atul Amaliyah Gerumpung, and 3) to determine the role of teacher professional competence in learning achievement group A students in TK Al Jami'atul Amaliyah Gerumpung. This study used a qualitative type of research by taking locations in Al Jami'atul Amaliyah Gerumpung Kindergarten. Collecting data using the method of observation, interviews and documentation. The research subjects in this study were group teachers, school principals and students. The data analysis technique is carried out interactively and continuously until it is complete to the point of data saturation. Checking the validity of the data is done by triangulating the data. The results of this study at the Al Jami'atul Amaliyah Gerumpung Kindergarten show that the role of the professional teacher in improving the quality of student learning, especially in professional teacher competence includes five aspects, namely: 1) mastering material, structure, concepts, and scientific mindsets that support the subjects being taught , 2) mastering competency standards and basic competencies of the subjects being taught, 3) developing learning materials taught creatively, 4) developing professionalism on an ongoing basis by taking reflective action, and 5) utilizing information and communication technology to develop oneself. Research in class A regarding the impact of teacher professionalism in improving student learning achievement at Al Jami'atul Amaliyah Gerumpung Kindergarten is very influential and every year most of it has increased. This can be observed from the results of the total value at the end of the semester in the last year which always increases.